Representasi Bullying dalam Film “Anyone Anywhere” Menggunakan Analisis Semiotika Charles Sanders Peirce - Ade Leasfita; Laurencia Goliesman (MUKASI: Jurnal Ilmu Komunikasi, 2025)
The school environment should be a safe place for children. However, in reality, it is one of the places where bullying occurs, as in the short film "Anyone anywhere" where bullying is experienced by a student. The aim of this research is to understand the representation of bullying in the short film "Anyone Anywhere" using Charles Sanders Peirce's semiotic analysis method with a qualitative approach and the theory used by Charles Sanders Peirce's semiotic theory. This research uses Charles Sanders Peirce's semiotic analysis with a meaning triangle (triadic) consisting of sign, object and interpretant. Through this research, several representations of bullying were found. In the sign there are 15 scenes in the form of non-verbal bullying consisting of kicking a ball at the victim, dousing the victim with water, grabbing, pushing, manipulating, dragging, intending to pin the finger with a piano cover, hitting the head repeatedly, choking, and slapping. In the object there are 5 scenes in the form of verbal bullying consisting of criticizing, threatening to blame, cornering, mocking and cursing. Finally, in the interpretant, there are 3 scenes in the form of psychological bullying which consists of giving cynical looks, mocking laughter, intimidation, scaring, and cynical smiles.